Influence of Ethanol Organosolv Pulping Conditions on Physicochemical Lignin Properties of European Larch. (3rd February 2019) - Hochegger, Markus; Cottyn-Boitte, Betty; Cézard, Laurent; Schober, Sigurd; Mittelbach, Martin
Abstract : Over the years, the organosolv pulping process has proven to be a valuable pretreatment method for various lignocellulosic feedstocks. The objective of this study was to characterize and assess the potential applicability of the organosolv lignin fraction from European larch sawdust, as no research has been conducted in this field so far. Eight different samples were prepared from the European larch sawdust under varied reaction conditions and one milled wood lignin sample as reference. The reaction temperature and sulfuric acid loading were varied between 420 and 460 K and 0.00 and 1.10% (w/w on dry wood basis) H2 SO4, respectively. The antiradical potential (via DPPH method), chemical structure (via ATR-FTIR, 1 H NMR, 31 P NMR, and thioacidolysis), as well as the molecular weight distribution of the isolated lignins were analyzed and compared. Results from thioacidolysis show a direct correlation between the amount of β -ether bonds broken and pulping process severity. Similarly, both antiradical potential and phenolic hydroxyl group content exhibit a direct relationship to reaction temperature and catalyst loading. On the contrary, the content of aliphatic hydroxyl groups and the average molecular weights both decreased with increasing process severity. The high content of phenolic hydroxyl groups and antioxidative potential of the larch organosolv fractions, especially for the sample isolated at 460 K and 1.10% H2 SO4 loading, indicate good applicability as antioxidants as well as feedstocks for further downstream valorization and require additional research in this area.